Методичний підхід до оптимізації витрат будівельних підприємств в умовах невизначеності - Сорокіна, Л. В.; Гойко, А. Ф. (Ways to Improve Construction Efficiency, 2014)
The basic directions of using the theory of fuzzy optimization to improve financial planning and monitoring of its implementation of construction enterprises. The methodical approach to determining the optimal level of costs UAH 1 construction products under fuzzy information about the objectives and constraints.